2016
DOI: 10.7150/ijbs.15438
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Neoadjuvant Chemoradiotherapy for Locally Advanced Rectal Cancer

Abstract: Neoadjuvant chemoradiotherapy has become the standard treatment for locally advanced rectal cancer. Neoadjuvant chemoradiotherapy not only can reduce tumor size and recurrence, but also increase the tumor resection rate and anus retention rate with very slight side effect. Comparing with preoperative chemotherapy, preoperative chemoradiotherapy can further reduce the local recurrence rate and downstage. Middle and low rectal cancers can benefit more from neoadjuvant chemradiotherapy than high rectal cancer. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
136
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(143 citation statements)
references
References 63 publications
2
136
0
5
Order By: Relevance
“…We suggested that stage III rectal SRCC should be arranged for PRT. It could reduce the tumour volume and may facilitate the tumour resection, block the tumour invasion like lymph nodes metastasis or mesorectal fascia threatened, and reduce the local recurrence rate37.…”
Section: Discussionmentioning
confidence: 99%
“…We suggested that stage III rectal SRCC should be arranged for PRT. It could reduce the tumour volume and may facilitate the tumour resection, block the tumour invasion like lymph nodes metastasis or mesorectal fascia threatened, and reduce the local recurrence rate37.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is an efficient option to treat earlier stages of CRC, but, most patients have been diagnosed at higher and advanced stages of the disease. Over the past decade chemoradiation therapy (CRT), synergistic effects of chemotherapy drugs and radiation, often in combination with surgery have been used as an effective CRC treatment for patients with Stages II and III (Li et al, ). Although, the use of CRT before surgical resection have yielded decreased risk for recurrence, shrinking tumor size, and also a better prognosis, but in over 90% of patients with higher stages of the disease the success rate faced with failure because of resistance to treatment (Geng & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nRCTx leads to a decrease of the tumor mass, allowing for a higher rate of sphincter sparing surgical methods and a higher rate of R0-resections. 4,5 The histological tumor regression (TRG) grade according to Dworak 6 serves as a system to categorize therapy-induced effects within rectal cancers after nRCTx. 7 Studies demonstrated the clinical relevance as a prognostic factor showing improved disease-free survival after pathologic response.…”
Section: Introductionmentioning
confidence: 99%